SOCIAL MOBILITY IS AN ISSUE OF IMPLEMENTATION OF HUMAN RIGHTS AND INTERESTS (American Journal of Research in Humanities and Social Sciences, 2023)
The article examines the significance and role of social mobility in the development of society. The article attempts to clarify the concept of social mobility, its types, directions, and channels. The factors that influence the implementation of social mobility have been studied. The consequences of the marginal situation arising in the process of mobility have been analyzed. The article concludes with recommendations based on the analysis of social mobility processes.